Probabilistic Q-margin Calculations Considering Dependency of Uncertain Load and Wind Generation - Jung-Uk Lim (International Journal of Applied Power Engineering (IJAPE), 2013)
This paper presents a novel probabilistic approach for computation of the reactive power margin (or Q-margin) of a power system with large-scale uncertain wind generation. Conventionally, Q-margin has been used as an index for indicating the system voltage stability level on system operation and planning. The conventional Q-margin method needs to be modified to fully accommodate uncertainties due to wind generation. This paper proposes a new Q-margin computation method using Q-matrix and the expected Q-margin (EQM). Q-matrix is a generic uncertainty matrix representing a discrete joint distribution of load and wind generation and the EQM, calculated from the Q-matrix, is a specific probabilistic variable that supersedes the conventional Q-margin. The proposed method is verified with the IEEE 39-bus test system including wind generation.